Effectiveness of local support for the adoption of a national programme – a descriptive study - Christopher Pearce; Jenny Bartlett; Adam McLeod; Paula Eustace; Rod Amos; Marianne Shearer (Journal of Innovation in Health Informatics, 2014)
Background Change management in health care is a complex and time-consuming endeavour, and no less so in implementing technological systems. In deploying a nationwide programme, the personally controlled electronic health record (PCEHR), the Australian Government employed a number of national and local change management programmes. Objective This article describes the processes undertaken and the experiences of introducing the PCEHR into 74 general practices across a specific area of metropolitan Melbourne. Method An online survey was developed by an independent evaluator and offered to all participating practices. The response rate was 82%. Results The deployment and testing of the eHealth infrastructure and the roll- out of the PCEHR were deeply supported through face-to-face, locally contextualised support processes. The area Medicare Local (ML), an organisation that provides support services to general practice and allied health in the community, provided support and programme coordination. This support occurred in the environment of a number of other initiatives to improve adoption. Conclusion The impact and value of this support in the registration and adoption process was explored in an online survey and found to be the key factor in practice engagement and success. ML support was seen as instrumental in improving adoption and was more effective than other activities. This article highlights the role of local support, in this case, MLs, in the effective implementation of eHealth programmes across a range of stakeholder groups, in particular, general practice, and the potential for the lessons learned from the engagement model of such an entity to be more generally applied.